Effectiveness of Evaluation Models in Measuring Mathematical Ability in the Digital Era: Literature Analysis - 'Afifah, Nur; Harahab, Ahmad Rifai (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze various evaluation models that are effective in measuring students' mathematical abilities. This literature review is based on literature from relevant international and national journals. The results of the study indicate that performance-based evaluation, adaptive tests, and diagnostic approaches are methods that can improve accuracy in assessing students' abilities. Performance-based evaluation allows for the measurement of analytical and problem-solving abilities through real tasks. Computer-adaptive tests offer efficiency and personalization in the evaluation process, while diagnostic approaches help identify misconceptions for more appropriate interventions. The combination of these three methods can provide more holistic results. This article is expected to provide guidance for educators in choosing the appropriate evaluation model to improve the quality of mathematics education